Design and development of the network OA＆M system based on SDN - Shun WU; Hui ZHANG; Ningzhe XING; Wei SONG; Tianlin HUANG; Yazhe TANG (Dianxin kexue)
The OA＆M systems of network infrastructure in electric power companies have drawbacks such as weak functions，coarse-grained monitor and control on the underlying networks and bad support on service deployment.SDN technology was used to solve these problems.An SDN-based OA＆M framework was presented，a cross-domain SDN network was built and the corresponding OA＆M system was developed，which could perform functions like topology discovery and fault detecting along with backup components switching.The experiments results prove that the OA＆M system can overcome the above drawbacks and achieve the design goal.